Outcomes of ultrasound-indicated cerclage in twin pregnancies with a short cervical length - Fang-Tzu Wu; Ying-Yu Chen; Chie-Pein Chen; Fang-Ju Sun; Chen-Yu Chen (Elsevier, 2020)
Objective: To investigate the outcomes of ultrasound-indicated cerclage in dichorionic-diamniotic (DCDA) twin pregnancies with a short cervical length. Materials and methods: This was a retrospective cohort study of DCDA twin pregnancies with a short cervical length (≤25 mm) from January 2000 to July 2017 to compare maternal and neonatal outcomes. Additional sub-analysis was performed by dividing the patients into two subgroups by a cervical length ≤15 mm and between 16 and 25 mm. Results: One hundred and eight women were initially diagnosed with twin pregnancies and cervical insufficiency. After excluding cases not meeting the study criteria, 46 women were recruited for analysis, of whom 33 underwent ultrasound-indicated cerclage. The delivery age of the cerclage group was significantly later than the non-cerclage group (34.85 ± 3.91 versus 31.08 ± 5.25 weeks, p = 0.011), and the latency was significantly longer in the cerclage group than in the non-cerclage group (86.09 ± 41.32 versus 52.31 ± 33.24 days, p = 0.014). Sub-analysis revealed that these benefits were significant in the subgroup of a cervical length ≤15 mm. Both first twin (twin A) and second twin (twin B) had a significantly decreased rate of neonatal intensive care unit admission in the cerclage group. However, twin A had more promising outcomes with significantly decreased rates of neonatal respiratory distress syndrome (6.7% versus 50.0%, p = 0.004) and sepsis (0% versus 25.0%, p = 0.019). Conclusion: Ultrasound-indicated cerclage in DCDA twin pregnancies can decrease preterm birth and prolong the latency. It also decreases neonatal morbidity, and is especially beneficial for twin A.